Stroke and Novel Coronavirus Infection in Humans: A Systematic Review and Meta-Analysis - Lee, Kai Wei; Yusof Khan, Abdul Hanif Khan; Ching, Siew Mooi; Chia, Peck Kee; Loh, Wei Chao; Abdul Rashid, Anna Misya'il; Baharin, Janudin; Inche Mat, Liyana Najwa; Wan Sulaiman, Wan Aliaa; Devaraj, Navin Kumar; Sivaratnam, Dhashani; Basri, Hamidon; et al. (Frontiers in Neurology, 2020)
As the world witnessed the devastation caused by the coronavirus disease 2019 (COVID-19) outbreak, a growing body of literature on COVID-19 is also becoming increasingly available. Stroke has increasingly been reported as a complication of COVID-19 infection. However, a systematic synthesis of the available data has not been conducted. Therefore, we performed a systematic review and meta-analysis of currently available epidemiological, clinical and laboratory data related to both stroke and COVID-19 infection. We systematically searched Medline, Cinahl and PubMed for studies related to stroke and COVID-19 from inception up to 04th June 2020. We selected cohort studies, case series and case reports that reported the occurrence of stroke in COVID-19 patients. A fixed-effects model was used to estimate the pooled frequency of stroke in COVID-19 patients with a 95% confidence interval (CI). Twenty-eight studies were included in the systematic review and seven studies for the meta-analysis. The pooled frequency of stroke in COVID-19 patients was 1.1% (95% CI: 0.8, 1.3). The heterogeneity was low (I2 = 0.0%). Even though the frequency of stroke among patients having COVID-19 infection was low; Those with concomitant COVID-19 infection and stroke suffered from a more severe infection and eventually had a poorer prognosis with a higher mortality rate (46.7%) than COVID-19 alone. Many COVID-19 patients shared the common traditional risk factors for stroke. We noted that ischemic stroke involving the anterior circulation with large vessels occlusion is the most common type of stroke with more strokes seen in multi-territorial regions, suggesting systemic thromboembolism. An elevated level of D-dimers, C-reactive protein, ferritin, lactic acid dehydrogenase, troponin, ESR, fibrinogen and a positive antiphospholipid antibody were also noted in this review. The occurrence of stroke in patients with COVID-19 infection is uncommon, but it may pose as an important prognostic marker and indicator of severity of infection, by causing large vessels occlusion and exhibiting a thrombo-inflammatory vascular picture. Physicians should be made aware and remain vigilant on the possible two-way relationship between stroke and COVID-19 infection. The rate of stroke among patient with COVID-19 infection may increase in the future as they share the common risk factors.